A theoretical model and experiment validation on filtration characteristics of methyl iodide in bubble column. (November 2017) - Wen, Jiming; Gu, Haifeng; Sun, Zhongning; Zhou, Yanmin
Highlights: A model is established to calculate decontamination factor for methyl iodide in bubble column accurately. Evaporation phenomenon is proved to suppress mass transfer from gas to liquid. Gas superficial velocity has different effect as its magnitude is different. Pressure has no effect on decontamination of methyl iodide in bubble column. Abstract: Bubble column is a potential method of filtering methyl iodide which is tough to be removed by Filter Containment Venting System. The filtering performance of bubble column is related to many factors including gas superficial velocity, temperature, pressure, gas component, etc. In order to clarify the association of decontamination factor (DF) of bubble column with these key factors, a theoretical model is established and a set of experiments are taken to validate the model. The model divides the filtration process in bubble column into two parts: mass transfer from bubble to solution and chemical reaction in solution. Therefore DF is determined by mass transfer resistance and chemical reaction resistance. Under most conditions, decontamination factor values calculated by the model are consistent with experimental results except the condition where there is intense evaporation at bubble surface. Under poor condition for model calculation precision, model calculation value is larger obviously than experimental results and the variation trend referring to model is even adverse to that of experiment as approaching boiling point. This is because evaporation phenomenon at bubble surface can restrain the filtration efficiency of bubble column significantly. The experimental results indicate that decontamination factor decreases obviously with the gas superficial velocity increase below 0.1 m/s but becomes insensitive to the gas superficial velocity above 0.1 m/s. Different from previous research conclusions, the influence of pressure on filtration efficiency for methyl iodide is proved experimentally to be so weak that decontamination factor is considered to be independent on pressure. Under different conditions, improving liquid level height is always an effective method of increasing the decontamination factor of bubble columns.